Penerapan Model Pembelajaran Berorientasi Pasar (Market Oriented Model) di SMK Ananda Mitra Industri Deltamas - Kiki Saepul Anam; Feri Hidayatullah Firmansyah; Audrina Famanda; Citra Ayu Puspita; Putri Sabila Al Asyifa (Journal on Education, 2023)
This research aims to obtain information about the implementation of market-oriented learning models at SMK Ananda Mitra Industri Deltamas. This research uses qualitative methods, namely research that produces descriptive data in the form of written or spoken words from individuals and observed behavior. The research procedure begins with the pre-field stage in the form of literature review and pre-observation, then the data collection stage using interviews, as well as observation and documentation studies to strengthen primary data and ends with data processing and analysis. The Ananda Mitra Deltamas Vocational High School (SMK) is an industry-based vocational school located in the Deltamas Cikarang Industrial Estate which is flanked by several industrial areas including GIIC, KITIC, Silicon, Jababeka, Hyundai, MM2100. Judging from the model used, this school implements a link and match education system. Because not many in Indonesia apply the market orientation model, based on the description above, this research will focus on observing the application of the market orientation model at SMK Ananda Mitra Deltamas. The results showed that: 1) the learning process at SMK Ananda Mitra Industri Deltamas refers to the 2013 curriculum which was further developed based on input from the industry in accordance with the vision and mission of the school and uses a block system, 2) Application of market-oriented learning models in SMK Ananda Mitra Industri Deltamas is designed and adapted to link and match with DUDI, and 3) There is a Special Employment Exchange (BKK) which is intended for class XII students as a means of placing work positions for each graduate.